2012
DOI: 10.1159/000338846
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-Resistant Tuberculosis in an Adult with Cystic Fibrosis

Abstract: Mycobacterium tuberculosis infection in patients with cystic fibrosis (CF) is rare. We report a 22-year-old CF patient with high fever, dyspnea and weight loss that progressively worsened over 2 weeks before admission. The patient suffered from liver cirrhosis, was colonized with Pseudomonas aeruginosa and had been repeatedly hospitalized for pulmonary infections. The patient was treated initially as for an exacerbation of P. aeruginosa infection, but tuberculosis (TBC) was suspected due to lack of improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…BCG infection has never been reported in these patients, even in countries with mandatory BCG vaccination policies and a relatively high prevalence of CF, such as France. Infections with M.tb have been reported, mostly in adults but also, more rarely, in children . Overall, changes in the integrity of the lung may increase susceptibility to mycobacterial infections, including TB.…”
Section: Inherited Conditions Affecting the Lungs And Conferring A Prmentioning
confidence: 99%
“…BCG infection has never been reported in these patients, even in countries with mandatory BCG vaccination policies and a relatively high prevalence of CF, such as France. Infections with M.tb have been reported, mostly in adults but also, more rarely, in children . Overall, changes in the integrity of the lung may increase susceptibility to mycobacterial infections, including TB.…”
Section: Inherited Conditions Affecting the Lungs And Conferring A Prmentioning
confidence: 99%
“…There is little information about pulmonary tuberculosis in CF patients, and only a few cases have been published [ 2 - 8 ]. The isolation rates of MTBC from respiratory samples of these patients were reported as 1.34-3.41% [ 3 , 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two of these strains were susceptible to pyrazinamide, while one strain was resistant. In the case report by Manika et al [ 8 ] the strain was found resistant to streptomycin, isoniazid, rifampicin, ethambutol, pyrazinamide and quinolones, while it was susceptible to amikacin, kanamycin and capreomycin. In the current study all of MTBC isolates were found to be susceptible to streptomycin, isoniazid, rifampicin, and ethambutol.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations